Navigating Complexity Coastal Tourism Governance in Indonesia: A Literature Review - Maulana, Muhammad Iqbal; Handika, Yola Rezki; Laila, Elvi Nur Nujumul; Negoro, Abul Haris Suryo (Proceeding International Conference on Religion, Science and Education, 2026)
This research aims to explore the potential of coastal tourism in Indonesia from the perspective of sustainable community empowerment. This research uses a qualitative method with the main data source of 20 Scopus-indexed articles spanning 2020-2024. Data analysis was carried out using the Nvivo 12 Plus tool. The results of this study show that Sustainable Cultural Tourism can be used as a sustainable community-based coastal tourism management strategy in Indonesia. Through this approach, in addition to providing economic impacts for the community, it also simultaneously contributes to maintaining local wisdom and environmental sustainability. The findings that have been identified show that government policies in empowering coastal communities through tourism potential are still running partially. An approach that can integrate social, economic, and environmental dimensions is needed to achieve the goal of sustainable coastal community empowerment. Active participation of the community supported by the seriousness of the government is the key to success in ensuring that coastal potential can be managed optimally. Success in community-based coastal tourism management can contribute positively to the country's economy while bringing independence and prosperity to local communities. Government support through policies, budgets, and assistance is essential for effective empowerment efforts.